A REVIEW OF THE GENUS MEGAELOSIA (ANURA, LEPTODACTYLIDAE) WITH A DESCRIPTION OF A NEW SPECIES - Giaretta, A. A.; Bokermann, WCA; Haddad, CFB (Soc Study Amphibians Reptiles, 1993)
A new species of Megaelosia is described from the Atlantic Forest in the northern part of São Paulo, southeastern Brazil. Based on examination of topotypic specimens of Megaelosia massarti, this species is removed from the synonymy of M. goeldii. Tadpoles of M. lutzae and M. massarti are described and natural history observations of M. massarti and M. goeldii are reported. Diagnoses, measurements, figures, distributional data, and a key for the species of Megaelosia are provided.